PENGARUH BOARD GENDER DIVERSITY, BOARD SIZE, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK - Robby Krisyadi; Vivian vivian (JURNAL AKUNTANSI, 2022)
This study aims to research whether board gender diversity, board size and leverage have influences on tax avoidance. This research involves a purposive sampling method and obtains 1660 company data listed on the Indonesia Stock Exchange (IDX) that met the sample criteria for the period 2017-2021. The results showed that tax avoidance in Indonesia do not influence board size, board gender diversity and leverage.